Reappraisal of the Federal Reserve discount mechanism. - Board of Governors of the Federal Reserve System (U.S.) ([Washington : Federal reserve system, 1971)
This book deals with the study of the secondary market for states and local government securities. Its a detailed account of some of the activities of the federal reserve bank of Washington.
Includes bibliographies.
oo 21/01/2019
Loans
Keywords: Federal Reserve banks; Discount